Peradilan Pidana Anak di Indonesia: Analisis terhadap Perlindungan Dan Implementasi Upaya Diversi - Aman Santoso; Hartoyo Hartoyo; Moh. Taufik (Lembaga Pengembangan Kinerja Dosen, 2025)
Juvenile criminal justice in Indonesia is an important aspect of the justice system that focuses on protecting the rights of children in conflict with the law. One of the efforts regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA) is diversity, which aims to prevent children from the judicial process that can harm their future. This study aims to analyze the protection of children's rights in the criminal justice process, as well as the implementation of diversity in the juvenile criminal justice system in Indonesia. The method used in this study is a qualitative approach with descriptive analysis, through literature studies and interviews with various related parties, such as judges, prosecutors, and community counselors. The results of the study indicate that although there are efforts to protect children's rights in criminal justice, the implementation of diversity still faces a number of challenges, including a lack of understanding among law enforcement officers, limited facilities, and a mismatch between policies and practices in the field. This study suggests the need to increase the capacity of law enforcement officers and other stakeholders in understanding and implementing diversity efforts optimally, as well as the need for policy evaluation to improve the effectiveness of child protection in criminal justice.